Recycled Polypropylene Improved with Thermoplastic Elastomers - Ecaterina Matei; Maria Râpă; Árpád Andor Andras; Andra Mihaela Predescu; Cristian Pantilimon; Alexandra Pica; Cristian Predescu (International Journal of Polymer Science)
The use of recycled polypropylene (RPP) as raw material for various industries has been known. However, the mechanical and thermal properties of recycled products are lower than those of raw material. The objective of this study was to obtain and investigate the modified recycled polypropylene (RPP) with commercial elastomers for possible applications. The compounded RPP-based thermoplastic elastomers were investigated in order to determine their thermal properties (melt flow index (MFI), differential scanning calorimetry (DSC), VICAT softening temperature (VST), and heat deflection temperature (HDT)), structural characteristics (optical microscopy, atomic force microscopy (AFM), and X-ray diffraction (XRD)), and mechanical properties (tensile properties, density, and IZOD impact). The RPP compounded with 10% elastomer recorded higher tensile properties than the unmodified RPP. Also, IZOD impact strength increased from 4.3±0.2 kJ/m2 (registered for RPP) to 21.7±2.5 kJ/m2 for the PPR/SIS30 compound, while the degree of crystallinity decreased for all compounds. The obtained results recommend the RPP/elastomers compounds both for environmental remediation from postconsumer PP wastes and to realize new goods with high performance for various applications.